2019
DOI: 10.1136/rapm-2018-100221
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and dexmedetomidine as adjuvants to local anesthetic mixture in intercostal nerve block for thoracoscopic pneumonectomy: a prospective randomized study

Abstract: Background and objectivesPerineural dexamethasone or dexmedetomidine prolongs the duration of single-injection peripheral nerve block when added to the local anesthetic solution. In a randomized, controlled, double-blinded study in patients undergoing thoracoscopic pneumonectomy, we tested the hypothesis that combined perineural dexamethasone and dexmedetomidine prolonged the duration of analgesia as compared with either perineural dexamethasone or perineural dexmedetomidine after intercostal nerve block (INB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 25 publications
5
65
0
1
Order By: Relevance
“…As mentioned previously, Cummings et al described an improvement with the addition of either dexamethasone or dexmedetomidine to the local anesthetic injectate; they were unable to demonstrate a significant difference in postoperative analgesia between the two adjuvants [2]. However, Zhang et al, in their prospective randomized study, demonstrated a significantly prolonged analgesic effect when using the Dex-Dex adjuvant technique for the intercostal nerve block [5]. Our three cases achieved similarly prolonged perioperative analgesia, but a notable difference is the type of regional block we provided our patients, which was the interscalene block in order to provide sufficient regional anesthesia to the site of surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As mentioned previously, Cummings et al described an improvement with the addition of either dexamethasone or dexmedetomidine to the local anesthetic injectate; they were unable to demonstrate a significant difference in postoperative analgesia between the two adjuvants [2]. However, Zhang et al, in their prospective randomized study, demonstrated a significantly prolonged analgesic effect when using the Dex-Dex adjuvant technique for the intercostal nerve block [5]. Our three cases achieved similarly prolonged perioperative analgesia, but a notable difference is the type of regional block we provided our patients, which was the interscalene block in order to provide sufficient regional anesthesia to the site of surgery.…”
Section: Discussionmentioning
confidence: 97%
“…A newer approach that currently has very limited literature is the combination of dexamethasone and dexmedetomidine (Dex-Dex) as the adjuvant to peripheral nerve blocks (PNB) [3,4]. In their prospective randomized study, Zhang et al demonstrate the prolongation of analgesia with use of a Dex-Dex combination adjuvant to ropivacaine in intercostal nerve blocks [5]. Given the limited literature, aside from a few case reports of different PNB and the previously mentioned prospective study, we present a case series of three patients, with their consent, who all received an interscalene block under ultrasound guidance for procedures involving the shoulder and proximal upper extremity.…”
Section: Introductionmentioning
confidence: 99%
“…Another study observed the effect of the Dex-Dex block in intercostal nerve blocks for thoracoscopic pneumonectomy. Zhang et al found that patients who received the Dex-Dex combination had approximately 3.5 more hours of postoperative pain relief and required significantly less fentanyl after surgery when compared to dexmedetomidine and dexamethasone groups [ 6 ]. Additionally, other case reports have demonstrated a prolonged analgesic effect when using the Dex-Dex combination in interscalene and transversus abdominis plane blocks [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our case illustrates the synergistic effect of a Dex-Dex adjuvant combination with local anesthetic injectate when used in a regional fascial plane block. Zhang et al found the analgesic effect to be prolonged with the use of the Dex-Dex technique for the intercostal nerve block [ 3 ]. Similarly improved and prolonged analgesia was demonstrated by using the Dex-Dex adjuvant for interscalene nerve blocks for surgeries of the upper extremity [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al provide one of the few studies to date demonstrating the efficacy of the Dex-Dex combination in PNB, which in their case was for an intercostal nerve block. They concluded that patients who received the Dex-Dex combination in the PNB experienced prolonged perioperative analgesia with no significant increase in adverse outcomes when compared to the groups only receiving PNB and no adjuvants, PNB with only dexamethasone, or PNB with only dexmedetomidine [ 3 ]. There are also a limited number of case reports in the literature supporting the claim that there exists a synergistic effect on the PNB’s duration of action that significantly supersedes the efficacy of using either one of these adjuvants alone [ 1 , 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%